Penerapan Media Gambar sebagai Upaya Peningkatan Kosakata Bahasa Inggris Siswa Pasca Pandemi Covid-19 - Fujiono; Reny Rosalina Rahmawati; Ainur Rofiq Hafsi (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPLEMENTING PICTURE MEDIA TO IMPROVE THE STUDENTS’ VOCABULARY AFTER THE COVID-19 PANDEMIC. After the Covid-19 pandemic, teachers and students have taken an opportunity to learn English more, especially vocabularies. Unfortunately, almost all of students were still confused and bored with their vocabulary learning; as a result that the students had low vocabularies. Additionally, teachers still used the conventional strategy to teach the vocabularies to their students, such as asking the students to memorize vocabulary in front of the class. Dealing with the issues, the writers have designed some methods, techniques, and strategies to improve the students’ vocabularies. The writers implemented picture media and asked the students to guess the picture using “What is it?”, almost all of students were enthusiastic to answer and write down the vocabulary in blackboard. The teaching-learning process has described that the students were involved in English class. On the other hand, the students also felt easier to know things in English, and the teacher also got new methods, techniques, and strategies in increasing students’ vocabulary through picture media implementation. Therefore, the teacher was suggested to implement some media to improve the students’ interest and motivation when they learn English vocabulary.